A REMOTE HRV BASED ON IOT (Heart rate variability) MONITORINGSYSTEMFORHYPERTENSIVEPATIENTS - SREENIV ASULA, MUDE; JALAJAKSHI, Y.; Deepa, K. (International Journal of Psychosocial Rehabilitation, 2018)
HRV (heart rate variability) is a measure of the difference between consecutive heartbeats. Coronary disease complications, diabetes, autonomous dysrhythmic illness problems, including hypertension, and a wide variety of chronic degenerative medical diseases are all sensitive to HRV study. The doctor’s use of a diagnostic, prognosis tool, and the effectiveness of the treatment provided are all enhanced when HRVs are exposed to specific medical issues. Borderline individuals, including those with and without a cardiac history, are often at risk for stroke and high-risk cardiac death. When medical treatment is needed, monitoring HRV values in these high-risk circumstances may be helpful. This article describes a low-cost, simple-to-use remote HRV monitoring device for borderline hypertensive patients that utilizes Internet of Things (IoT) technology. HRV characteristics are extracted using an IoT-based pulse sensor in the proposed system.